Single-layer fluorinated MXene and preparation method thereof
By etching the reaction of Tin+1AlCn with fluorine-containing oligomer under ultrasonic assisted conditions, the time and efficiency problems in the preparation of MXene were solved, and the single-layer fluorinated MXene was efficiently prepared, which improved its dispersion in the dispersant Performance and raw material utilization.
Patent Information
- Application Number
- CN202411439736.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
AI Technical Summary
The preparation process of existing MXene takes a long time, has low raw material utilization, low efficiency, low yield of product single layer MXene and is prone to spontaneous agglomeration, which limits its dispersing performance in dispersants or substrates.
Tin+1AlCn is etched with HF aqueous solution and fluorine-containing oligomer under ultrasonic assisted conditions at room temperature. By reacting the acid halide end of the active reaction end group with the hydroxyl group on the surface of Tin+1CnTx, a single layer of fluorinated MXene is formed to eliminate hydrogen The bonds accumulate and improve dispersion.
Achieve rapid and efficient preparation of single-layer fluorinated MXene, with a fluorine content of up to 20%, maintaining good dispersion in a variety of solvents and polymer matrixes, significantly improving raw material utilization and product yield, reducing etching time and raw material consumption .
Smart Images

Figure CN119320138A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional fluorine-containing functional materials, and specifically relates to a single-layer fluorinated MXene and a preparation method thereof. Background Art
[0002] MXene is a new type of transition metal carbon / nitride two-dimensional nano-layered material with unique structure and physical and chemical properties. Since its discovery in 2011, it has been increasingly regarded as a new functional material and has attracted much attention. It has broad application prospects in the fields of energy storage and conversion, sensing, catalysis, and polymer composite functional materials. The general formula of MXene is M n+1 X n T x (n=an integer of 1 to 4), wherein M represents a transition metal such as Ti, Nb, Mo, V, etc., and X represents C and / or N; T x represents hydroxyl, fluorine and / or oxygen, by selectively etching the A layer (main group elements Al, Ga, In, Si, etc.) from the parent MAX phase and subsequently introducing T x Ti n+1 C n T x It is a typical representative of MXene. Generally, HF (or HF generated in situ such as HCl+LiF) is used to etch the precursor Ti n+1 AlC n , then (multiple times) centrifuged, and then separated from the supernatant (or suspension) after centrifugation.
[0003] Practice shows that the main problems or outstanding defects of the above preparation methods are as follows. First, the preparation process is time-consuming (24 to 48 hours) and inefficient; second, it is important to separate and obtain a single layer (or few layers) of Ti from the supernatant (or suspension) after centrifugation. n+1 C n T x , the precursor utilization rate is low, and the target product yield is low; thirdly, the (single or few-layer) Ti obtained by this method n+1 C n T x The surface has oxygen-containing groups such as -OH, and there are strong interlayer hydrogen bonds between these groups. Hydrogen bonds together with Van der Waals forces drive Ti n+1 C n T x The layers attract each other, resulting in the prepared (single or few layers) Ti n+ 1C n T x Once again, spontaneous reunion has largely limited Ti n+1 C nT x Highly dispersed in the dispersant or matrix, making it difficult to maximize the use of Ti n+1 C n T x Therefore, it is urgent to develop a method for efficiently preparing (single or few-layer) Ti with high dispersion and low agglomeration in research and application. n+1 C n T x new method.
[0004] The researchers tried to improve Ti by covalent modification. n+1 C n T x The dispersion degree in the dispersant or composite matrix is determined by introducing a modifier containing reactive groups to the Ti n+1 C n T x The surface hydroxyl groups react with each other, and the modifier molecules are grafted onto the Ti by covalent bonds. n+1 C n T x The literature (Tribology International, 2022, 170, 107500) reported a poly[2-(perfluorooctyl)ethyl methacrylate] grafted modified Ti3C2T x The method for preparing fluorinated MXene is characterized by: first, using HCl and LiF to in-situ generate HF to etch Ti3AlC2 precursor for 24 hours, centrifuging the reaction mixture, and freeze-drying the supernatant and the suspension for 48 hours to obtain Ti3C2T x Powder. Second, the obtained Ti3C2T x After the powder is alkalized, the surface hydroxyl groups react with the silane coupling agent 3-(methacryloyloxy)propyltrimethoxysilane (MPS) to graft MPS onto Ti3C2T through silicon-oxygen-silicon covalent bonds. x surface, and obtain MPS-modified Ti3C2T with polymerizable acrylate end groups on the surface x Third, Ti3C2T was modified by MPS. x The target product, fluorinated MXene, is obtained by copolymerization with poly[2-(perfluorooctyl)ethyl methacrylate]. This method is time-consuming, inefficient, has complicated preparation steps, low yield, and the obtained fluorinated MXene is mainly a multilayer structure.
[0005] The invention patent with publication number CN 116827164A discloses a method for preparing a friction nanogenerator based on F-MXene, which is characterized by using a monolayer MXene as a raw material and a fluorinated silane as a modifier, and obtaining a fluorinated MXene through a dehydration condensation reaction between the hydroxyl groups on the surface of the MXene and the fluorinated silane. However, the preparation efficiency and product yield of the required key raw material monolayer MXene are very low. Importantly, the surface of the key raw material monolayer MXene used has oxygen-containing functional groups such as hydroxyl groups, and there are hydrogen bonds and other interactions between these oxygen-containing functional groups, which causes the MXene to spontaneously agglomerate before and during the reaction and is difficult to maintain a single-layer structure. Therefore, in fact, the preparation of fluorinated MXene by this technology is not only inefficient and low in yield, but also the product is mainly a multilayer structure.
[0006] Hexafluoropropylene oxide oligomer (PHFPO) is a fluorine-containing polymer with unique structure, excellent performance and broad application prospects. Literature (Macromolecules, 2012, 45, 4907) shows that PHFPO can be prepared in a controllable manner by anionic ring-opening polymerization of hexafluoropropylene oxide (HFPO), and this preparation method is efficient, low-cost and has good selectivity. More importantly, the PHFPO prepared by anionic ring-opening polymerization of HFPO has an acyl fluoride group with high reactivity at the end. The acyl fluoride group can react quickly, efficiently and even stoichiometrically with functional groups such as hydroxyl and epoxy groups under mild conditions, and can introduce PHFPO into the target molecule in a targeted manner, which is of great significance for the design and efficient and controllable preparation of fluorine-containing functional materials. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the existing MXene, such as the long preparation process, low raw material utilization, low efficiency, low yield of the product single-layer MXene and easy spontaneous agglomeration. First, a single-layer fluorinated MXene with high fluorine content, adjustable structure and high dispersion in solvents and matrices is provided. Secondly, a preparation method for the single-layer fluorinated MXene with mild conditions, simple and efficient, and easy to industrialize is provided.
[0008] In order to solve the above technical problems, the single-layer fluorinated MXene provided by the present invention is prepared by the following method: at room temperature, Ti n+1 AlC n , HF aqueous solution, and fluorinated oligomers were added to a polytetrafluoroethylene beaker, and Ti was etched with HF under ultrasound-assisted enhanced mass transfer conditions. n+1 C n T x During the etching process, the fluorinated oligomer with active reaction end groups reacts with the Ti generated after etching. n+ 1C n T xThe surface hydroxyl groups react for 4 to 8 hours, and the obtained reaction mixture is centrifuged and the obtained solid phase is fully dried to obtain the target product, a single-layer fluorinated MXene.
[0009] The above-mentioned fluorinated oligomer is a perfluoroepoxy oligomer-based acyl halide or perfluoroanhydride, which mainly grafts a perfluoropolyether chain or a perfluoroalkyl chain to the MXene surface through an esterification reaction.
[0010] The general structural formula of the above-mentioned perfluoroepoxy oligomer-based acyl halide is R1-COX, wherein X is F or Cl, and R1 is wherein m is an integer from 1 to 15. When R1-COX is a hexafluoropropylene oxide dimer (m=2), the target product is recorded as F2-Ti n+1 C n T x MXene; when R1-COX is a trimer of hexafluoropropylene oxide (m=3), the target product is recorded as F3-Ti n+1 C n T x MXene, and so on.
[0011] The general structural formula of the above perfluoroanhydride is R2-COOCO-R2, where R2 is Wherein p is an integer from 1 to 7.
[0012] In the above method, Ti is preferably n+1 AlC n The value of n is an integer from 1 to 3.
[0013] In the above method, Ti is preferably n+1 AlC n The usage ratio of HF and fluorinated oligomer is 0.50~1.00g:0.01~0.02L:0.13~0.26L.
[0014] In the above method, the mass concentration of HF in the HF aqueous solution is preferably 30% to 50%.
[0015] In the above method, the reaction temperature is preferably 20 to 40°C.
[0016] In the above method, the drying temperature is preferably 30 to 80°C.
[0017] The beneficial effects of the present invention are as follows:
[0018] 1. The monolayer fluorinated MXene of the present invention has a controllable structure and excellent performance, and the fluorine content in the monolayer fluorinated MXene can reach 20%. The prepared fluorinated MXene has excellent dispersibility in a variety of solvents and polymer matrices, and can even maintain a good monolayer in a dry state.
[0019] 2. The method of preparing monolayer fluorinated MXene of the present invention is fast and efficient, with mild conditions, thorough reaction, high product yield and controllable structure (which can be controlled by the repeating unit structure and degree of polymerization of fluorinated oligomers), realizing the process of preparing monolayer fluorinated MXene from precursor Ti n+ 1AlC n The method of the present invention is to use HF to etch Ti under the condition of ultrasound-assisted enhanced mass transfer. n+1 AlC n Preparation of Ti n+1 C n T x At the same time, the fluorinated oligomer containing highly active reactive end groups is quickly transferred and diffused to the Ti generated after etching. n+1 C n T x Thereafter, the acyl halide end groups of the fluorinated oligomers are bonded to the Ti n+1 C n T x The hydroxyl groups generated on the surface react rapidly, and the fluorinated functional chains of the fluorinated oligomers are grafted onto Ti by esterification. n+1 C n T x The outstanding advantages of this preparation method are as follows: First, the preparation process consumes and converts Ti from the source. n+1 C n T x The surface hydroxyl groups of Ti n+1 C n T x Spontaneous aggregation caused by hydrogen bonding between layers; secondly, in view of the fluorinated Ti n+1 C n T x The special fluorine repulsion between the fluorinated oligomer chains grafted on the surface of (i.e., fluorinated MXene) causes the fluorinated MXene sheets to move away from each other, and ultimately makes the target product fluorinated MXene a single layer; thirdly, if the raw material is a fluorinated oligomer with an acyl fluoride end group, the by-product HF generated during the esterification reaction can also participate in the nearby precursor Ti n+ 1AlC n Further etching, which improves the etching rate while minimizing the consumption of raw material HF and improving the utilization rate of raw materials. n+1 AlC n is completely etched and fully converted (Ti n+1 AlC nThe conversion rate is close to 100%), and the etching rate is significantly accelerated (the etching process is sharply reduced from the publicly reported 24 to 48 hours to 4 to 8 hours), and the yield of the target product is also improved (the yield of single-layer fluorinated MXene exceeds 90%). More importantly, the special and effective fluorine repulsion between the fluorinated monolayer MXene prepared by the present invention inhibits or prevents the agglomeration between the fluorinated monolayer MXene, and maximizes its dispersion performance in matrices such as dispersants and polymers. Using it for the preparation of composite materials can significantly improve the utilization rate of MXene and the performance of the corresponding composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is the X-ray diffraction spectrum of the precursor Ti3AlC2 and the monolayer fluorinated MXene in Examples 1-2.
[0021] Figure 2 This is an atomic force microscope image of a single layer of fluorinated MXene in Example 1.
[0022] Figure 3 It is the X-ray photoelectron spectrum of the precursor Ti3AlC2 and the monolayer fluorinated MXene in Examples 1-2.
[0023] Figure 4 This is an atomic force microscopy image of a single layer of fluorinated MXene in Example 2. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0025] Example 1
[0026] At room temperature, 0.5 g Ti3AlC2, 10 mL of 49.9% HF aqueous solution, and 130 mL of hexafluoropropylene oxide dimer containing acyl fluoride end groups (CF3CF2CF2OCF(CF3)COF, provided by Zhejiang Huanxin Fluoro Materials Co., Ltd.) were added to a polytetrafluoroethylene beaker, and reacted for 5 h at room temperature (25 ° C) with the assistance of ultrasound. The reaction mixture was centrifuged, and the obtained solid was washed with deionized water until it was nearly neutral, and then dried at 60 ° C for 12 h. The obtained hexafluoropropylene oxide dimer fluorinated monolayer MXene (i.e., monolayer fluorinated MXene) was recorded as F2-Ti3C2T x MXene with a yield of 90%.
[0027] The precursors Ti3AlC2 and F2-Ti3C2T were characterized by X-ray diffraction, X-ray photoelectron spectroscopy and atomic force microscopy. x MXene structure, results see Figures 1 to 3 .
[0028] Figure 1 The X-ray diffraction spectrum results show that the precursor Ti3AlC2 presents a typical MAX phase structure. After etching and fluorination, the main peak of Ti3AlC2 phase corresponding to the (104) crystal plane at 2θ of 39.2° and the peaks of Ti3AlC2 corresponding to other crystal planes disappear, and the F2-Ti3C2T x MXene has no obvious diffraction peaks in the range of 5° to 80° at 2θ, indicating that the original classic MAX structure of Ti3AlC2 has become a single-layer structure after etching and fluorination. The single-layer structure of the target product is further confirmed by the characterization results of atomic force microscopy (see Figure 2 ). Figure 3 In the X-ray photoelectron spectroscopy, F2-Ti3C2T x MXene has a characteristic peak of F1s at 686.0eV, indicating that the perfluoropolyether chain of hexafluoropropylene oxide dimer CF3CF2CF2OCF(CF3)C(O)- has been successfully grafted on the MXene surface. At the same time, the disappearance of the original Ti3AlC2 peak corresponding to Al 2p at 71.3eV confirms Figure 1 The results show that the Al in the precursor Ti3AlC2 has been completely etched. In addition, the F content on the surface of F2MXene was measured to be about 18.03% by X-ray photoelectron spectroscopy. The above results prove the successful preparation of monolayer fluorinated MXene.
[0029] Example 2
[0030] In this example, 180 mL of hexafluoropropylene oxide trimer containing acyl fluoride end groups (CF3CF2CF2OCF(CF3)CF2OCF(CF3)COF, provided by Zhejiang Huanxin Fluoro Materials Co., Ltd.) was used to replace the hexafluoropropylene oxide dimer containing acyl fluoride end groups in Example 1, and the reaction time was extended from 5 h to 6 h. The other steps were the same as in Example 1 to obtain a fluorinated monolayer MXene of hexafluoropropylene oxide trimer (i.e., a monolayer fluorinated MXene), which was recorded as F3-Ti3C2T x MXene with a yield of 93%.
[0031] Figure 1 The X-ray diffraction spectrum of Figure 4 The atomic force microscopy characterization results are similar to those in Example 1, both of which prove that the precursor Ti3AlC2 has become a layered structure after etching and fluorination, and is a single layer. Figure 3The X-ray photoelectron spectroscopy characterization results also proved that the perfluoropolyether chain of hexafluoropropylene oxide trimer CF3CF2CF2OCF(CF3)CF2OCF(CF3)C(O)- has been successfully grafted on the MXene surface. In addition, the X-ray photoelectron spectroscopy was used to measure the x The F content on the MXene surface is 20.47%.
[0032] Example 3
[0033] In this embodiment, hexafluoropropylene oxide pentamer (CF3CF2CF2O (CF(CF3)CF2O) containing acyl chloride end groups is used. 13 CF(CF3)COCl) was used to replace the hexafluoropropylene oxide dimer containing acyl fluoride end groups in Example 1, the reaction time was extended from 5 h to 8 h, the reaction temperature was 40 ° C, and the other steps were the same as in Example 1 to obtain a hexafluoropropylene oxide pentamer fluorinated monolayer MXene, denoted as F 15 -Ti3C2T x MXene with a yield of 90%.
[0034] The synthesis method of hexafluoropropylene oxide pentadecamer containing acyl chloride terminal groups in this embodiment is as follows: under nitrogen protection and room temperature, hexafluoropropylene oxide pentadecamer containing carboxylic acid terminal groups (CF3CF2CF2O (CF(CF3)CF2O) 13 CF(CF3)COOH, provided by DuPont, USA) was added dropwise into thionyl chloride, and the mixture was refluxed at 80°C for 8 h under stirring. The remaining thionyl chloride was removed by vacuum distillation to obtain a pentamer of hexafluoropropylene oxide containing an acyl chloride terminal group.
[0035] Example 4
[0036] In this example, pentafluoropropionic anhydride (CF3CF2COOCOCF2CF3, provided by Shanghai MacLean Biochemical Technology Co., Ltd.) was used to replace the hexafluoropropylene oxide dimer containing acyl fluoride end groups in Example 1. The other steps were the same as in Example 1 to obtain a pentafluoropropionic anhydride fluorinated monolayer MXene, which was recorded as PFPA-Ti3C2T x MXene with a yield of 92%.
[0037] Example 5
[0038] In this example, heptafluorobutyric anhydride (CF3(CF2)2COOCO(CF2)2CF3, provided by Merck Life Sciences Ltd.) was used to replace the hexafluoropropylene oxide dimer containing acyl fluoride end groups in Example 1, the reaction time was extended from 5 h to 6 h, the reaction temperature was 35 ° C, and the other steps were the same as in Example 1 to obtain a heptafluorobutyric anhydride fluorinated monolayer MXene, which was recorded as HFBA-Ti3C2Tx MXene with a yield of 93%.
[0039] Example 6
[0040] In this example, nonafluoropentanoic anhydride (CF3(CF2)3COOCO(CF2)3CF3, provided by Beijing Fan De Biotechnology Co., Ltd.) was used to replace the hexafluoropropylene oxide dimer containing acyl fluoride end groups in Example 1, the reaction time was extended from 5 h to 6 h, the reaction temperature was 35 ° C, and the other steps were the same as in Example 1 to obtain a nonafluoropentanoic anhydride fluorinated monolayer MXene, which was recorded as NFPA-Ti3C2T x MXene with a yield of 92%.
[0041] Example 7
[0042] In this example, pentafluorooctanoic anhydride (CF3(CF2)6COOCO(CF2)6CF3, provided by Shanghai Myrel Biochemical Technology Co., Ltd.) was used to replace the hexafluoropropylene oxide dimer containing acyl fluoride end groups in Example 1, the reaction time was extended from 5 h to 8 h, the reaction temperature was 40 ° C, and the other steps were the same as in Example 1 to obtain a pentafluorooctanoic anhydride fluorinated monolayer MXene, which was recorded as PFTA-Ti3C2T x MXene with a yield of 90%.
[0043] Example 8
[0044] In this embodiment, Ti2AlC is used to replace Ti3AlC2 in Example 1, and the other steps are the same as in Example 1 to obtain a fluorinated monolayer MXene of hexafluoropropylene oxide dimer, which is denoted as F2-Ti2CT x MXene with a yield of 90%.
Claims
1. A method for preparing a single-layer fluorinated MXene, characterized in that: At room temperature, Ti n+1 AlC n , HF aqueous solution, and fluorinated oligomers are added to a polytetrafluoroethylene beaker and reacted for 4 to 8 hours under ultrasound assistance. The reaction mixture is centrifuged and the obtained solid phase is dried to obtain a monolayer fluorinated MXene; The above-mentioned fluorine-containing oligomer is a perfluoroepoxy oligomer-based acyl halide or a perfluoroacid anhydride; The general structural formula of the perfluoroepoxy oligomer-based acyl halide is R1-COX, wherein X represents F or Cl, and R1 represents Wherein m is an integer from 1 to 15; The general structural formula of the perfluoroanhydride is R2-COOCO-R2, where R2 represents Where p is an integer from 1 to 7; The Ti n+1 AlC n The value of n is an integer from 1 to 3.
2. The method for preparing a single-layer fluorinated MXene according to claim 1, characterized in that: The Ti n+1 AlC n The usage ratio of HF aqueous solution and fluorinated oligomer is 0.50~1.00g:0.01~0.02L:0.13~0.26L.
3. The method for preparing a single-layer fluorinated MXene according to claim 2, characterized in that: The mass concentration of HF in the HF aqueous solution is 30% to 50%.
4. The method for preparing a single-layer fluorinated MXene according to claim 1, characterized in that: The reaction was carried out at 20-40°C for 4-8 hours with the assistance of ultrasound.
5. The method for preparing a single-layer fluorinated MXene according to claim 1, characterized in that: The drying temperature is 30-80°C.
6. A single-layer fluorinated MXene obtained by any one of the preparation methods of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of friction nanometer generator based on F-MXene
CN116827164A